Urethanosil ionic nanocomposite gel conductors with an ionic liquid - Jovanovski, Vasko (Acta chimica slovenica, 2004)
The urethanosil semi-solid type of electrolyte with incorporated redox species (I-, I3-) was found to be appropriate as an intermediate layer between the WO3 working electrode and the Pt counter-electrode in hybrid electrochromic devices. Urethanosils were prepared by the sol-gel route from single end-capped alkoxysilane precursors, which were synthesized using mono ether terminated oligoethyleneglycols and isocyanatopropyltriethoxysilane. In the sol-gel processing of the redox electrolyte, besides the urethanosil precursor tetraethoxysilane served as a network former, oxalic acid as a gelation promoter, various iodidesž iodine as a source of redox species and triethyleneglycol as a non-volatile solvent. Time-dependent IR ATR measurements were performed to follow solvolysis and condensation of the organically modified silica framework. To take advantage of the high ionic mobility, negligible volatility, low viscosity and large electrochemical window, an ionic liquid (EtPrIm+I-) was also considered as a co-solvent and simultaneously as a source of the iodide redox moiety.
Keywords: elektrokemija; elektrokromizem; elektrokromni materiali; sol-gel postopki